Control of morphological and electrical properties of flexographic printed electronics through tailored ink rheology - Miles Morgan (Organic Electronics, 2019)
Functional model inks were formulated and printed using flexography in order to assess the influence of ink extensional elasticity and print velocity on the morphological and electrical properties of printed layers. Increased extensional elasticity and higher print velocity resulted in the printing of more isotropic prints, both morphologically and electronically. Furthermore, a correlation between the prints’ morphological and electrical anisotropy strongly suggests that print uniformity has a considerable influence on functionality and that ink rheology may be used to control such characteristics.